Analysis of Fire Emergency Response Readiness at Oil and Gas Company - Iwan Jatmika; Dzulkifli; Ahmad Ariq Atthaya; Sayyid Hasan; Muhammad Schehan Al Azhar (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Fire is one of the dangers that is often found in the oil and gas industry. A fire preparedness system is needed by companies to avoid dangers and risks that have the potential to cause damage, injury or death. Objective: This research aims to see the readiness of Fire Emergency Response system. The results of this research can be used as a basis for developing policies and programs Fire Emergency Response work. Method: This research uses the FERRAT Form as the basis for the research. The instrument used in this research is the FERRAT Form. Field observations were carried out to see directly the field conditions and the form filling process. Result: The results of this research show that the company's readiness in implementing the Fire Emergency Response system as a whole has reached an average of <90% with an overall value of 40.33%. Conclusion: It is hoped that with this research, companies can carry out independent evaluations and immediately initiate improvements related to risk-based system design, adequacy levels according to potential fire risks and ensuring emergency response equipment is always in a ready-to-operate and alert condition